Safe prescribing in cancer patients during the COVID‐19 pandemic: A new initiative from the UK Cancer Coronavirus Project (UKCCP) team. Issue 6 (8th December 2022) - Appanna, Nathan; Patel, Grisma; Burke, Emma; Burnett, Alexander; Clark, James; Mew, Rosie; Khan, Sam; Little, Martin; Liu, Justin; Panneerselvam, Hari; Patel, Vijay; Platt, James; et al.
Abstract :